Social Preferences and Strategic Uncertainty: An Experiment on Markets and Contracts - Cabrales, Antonio; Miniaci, Raffaele; Piovesan, Marco; Ponti, Giovanni (American Economic Review, 2010)
This paper reports a three-phase experiment on a stylized labor market. In the first two phases, agents face simple games, which we use to estimate subjects' social and reciprocity concerns. In the last phase, four principals compete by offering agents a contract from a fixed menu. Then, agents “choose to work” for a principal by selecting one of the available contracts. We find that (i) (heterogeneous) social preferences are significant determinants of choices, (ii) for both principals and agents, strategic uncertainty aversion is a stronger determinant of choices than fairness, and (iii) agents display a marked propensity to work for principals with similar distributional concerns. (JEL D82, D86, J41)